Development and validation of an LC-MS/MS method for quantitative analysis of mirtazapine in human plasma - Chorilli, Marlus [UNESP]; Bonfilio, Rudy [UNESP]; Louvadini, Caroline Rossim; Gonçalves, Francine; Salgado, Hérida Regina Nunes [UNESP] (Scientific Research, 2011)
Mirtazapine (MTZ) is an antidepressant drug, which belongs to the chemical class of piperazinoazepines. A liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was developed for the quantifica- tion of MTZ in plasma at the concentrations associated with therapy. Diazepam (DZP) was used as internal standard, added to 200 μL of plasma sample prior to a liquid-liquid extraction using hexane. Chroma- tographic separation was achieved on an Agilent® Eclipse XDB C-18 column (100 × 2.1 mm, 3.5 μm) in iso- cratic mode at 40?C. Mobile phase was 10 mM ammonium acetate/acetonitrile/formic acid (60/40/0.1, v/v/v) at a constant flow rate of 0.5 mL?min–1. The injection volume was 10 ?L and the total run time was 3.2 min. The method shows selectivity and linearity. The detection and quantitation limits were established at 0.17 and 0.50 ng?mL–1, respectively. The extraction recoveries for MTZ and DZP were found to be between 84.9 and 93.9%. The intra-day and inter-day precision and accuracy fulfill at the international acceptance criteria. The method shows to be stable for the studied parameters. Therefore, a rapid, specific, and sensitive LC-MS/MS method for quantification of MTZ in human plasma was developed and can be used in therapeu- tic drug monitoring of this drug.
Keywords: Mirtazapine; High-Performance liquid chromatography; Mass spectrometry; Human plasma